Fecal short‐chain fatty acid concentrations and dysbiosis in dogs with chronic enteropathy. (17th May 2019) - Minamoto, Yasushi; Minamoto, Tomomi; Isaiah, Anitha; Sattasathuchana, Panpicha; Buono, Agostino; Rangachari, Venkat R.; McNeely, Isaac H.; Lidbury, Jonathan; Steiner, Jörg M.; Suchodolski, Jan S.
Abstract: Background: Accumulating evidence shows an important relationship between the gastrointestinal (GI) microbiota and host health. Microbial metabolites are believed to play a critical role in host‐microbial interactions. Short‐chain fatty acids (SCFAs) are major end products of bacterial carbohydrate fermentation in the intestinal tract. Decreased concentrations of SCFAs have been observed in humans with GI disease. However, large‐scale clinical data in dogs are lacking. Hypothesis/Objective: To evaluate fecal concentrations of SCFAs and the fecal microbiota in healthy control (HC) dogs and dogs with chronic enteropathy (CE). Animals: Forty‐nine privately owned HC dogs and 73 dogs with CE. Methods: Prospective cohort study. Fecal concentrations of SCFAs were measured using gas chromatography/mass spectrometry. Illumina sequencing and quantitative real‐time polymerase chain reaction were utilized to evaluate the fecal microbiota. Results: Fecal concentrations (median [range] μmol/g of dry matter) of acetate were lower ( P = .03) in dogs with CE (185.8 [20.1‐1042.1]) than in HC dogs (224.0 [87.7‐672.8]). Propionate were also lower ( P < .001) in dogs with CE (46.4 [0.4‐227.9]) than in HC dogs (105.9 [1.6‐266.9]). Moreover, total SCFAs were lower ( P = .005) in dogs with CE (268.1 [21.8‐1378.2]) than in HC dogs (377.2 [126.6‐927.0]). Dysbiosis in dogs with CE was characterized by decreased bacterial diversity and richness, distinct microbial community clustering compared with that in HC dogs, and a higher dysbiosis index. Conclusions and Clinical Importance: Dogs with CE had an altered fecal SCFA concentration accompanied by significant changes of the fecal microbiota.